Strengthening Geber Pangaji Volunteers Efforts to Improve the Quality of Al-Quran Learning in Batukaras Village - Nenng Nuermalasari; Irpan Ilmi; Andi Abdul Hanafi; Shabilla Aulia Kurni; Alfi Salma Fauziya (PT FORMOSA CENDEKIA GLOBAL, 2023)
The Pangandaran Chapter of Indonesia Mengaji Collaboration which is realized under the name Pangandaran Mengaji Empowerment Movement (GEBER PANGAJI) is a program that seeks to eradicate Qur'an illiteracy, and consists of 2 main programs, namely intended for elementary-high school/K students, and for the community general.. The aim of this service is to: Improve the culture of Maghrib Koran recitation, realize the formulation of the Maghrib Koran program, and provide quality human resources in the religious field. Implementation of community. method with the following procedures: Brainstorming, Focus, Implementation, Evaluation and Reflection. The service target of 111 Geber Pangaji volunteers in Batukaras village, Pangandaran Regency, will be implemented in August 2023. The results of this community service are as follows; 1) increasing children's motivation to take part in Maghrib Koran recitation, 2) Implementation of optimizing the Geber Pangaji program in Pangandaran Regency, namely by having targets for achieving Maghrib Koran focusing on BTQ, Tahfidz and Fahmil Qur'an as well as an evaluation system 3) Implementation of training for Geber Pangaji volunteers.